Participação dos receptores de angiotensina II AT1 e AT2 no núcleo central da amígdala sobre a ingestão de sódio - Oliveira, Ludmila Corrêa Guimarães de (2017)
The central nervous system (CNS) plays an important role in maintaining the regulation of homeostatic mechanisms that control the osmolarity and volume of body fluids. The amygdala is a limbic structure of the brain circuit involved in the sodium and water intake control. Its structure is composed of several subnuclei: the basal , the medial , the lateral and the central . The importance of angiotensin receptors in the central nucleus of the amygdala (CeA) in regulating thirst and sodium appetite is poorly understood. Here we have evaluated the participation of angiotensina II (ANGII) receptors AT1 and AT2 in the CeA on water and sodium intake induced by sodium depletion. Wistar male rats (250-280g) were submitted to extracellular dehydration by subcutaneous injections of furosemide (10 mg/kg) and captopril (5mg/kg) (FURO+CAP). In rats treated with FURO+CAP, central microinjections (0,1 μl ) of either ANGII (48 pM), Compound 21 (AT2 receptor selective agonist - C21; 0.1 μM) or PD123319 (AT2 receptor antagonist, 40 mM) forty-five minutes after FURO+CAP treatment did not significantly change water intake (ANGII:3.3±1.2 vs. Control:2.5±0.9 ml/120 min; C21:4.7±1.3 vs. Control:4.6±0.9 ml/120 min; PD123319:6.1±1.7 vs. Control:6.2±1.3 ml/120 min). However, losartan (AT1 receptor antagonist, 217 mM) to potentiate water intake (losartan: 4.8±0.6 vs. Control:3.1±1.1 ml/120 min, p<0.05 between treatments). Sodium intake was not different following ANGII (48 pM), losartan (217 mM), C21 (0,1 μM) or PD123319 (40 mM) treatments. We also tested AT2 receptors activation or blockade in the CeA before the establishment of ANGII mechanisms caused by extracellular dehydration. Right after FURO+CAP treatment, we microinjected C21 or PD123319 and saw an impaired in sodium intake caused by selective activation of AT2 receptors (C21:3.5±0.9 vs Control:5.8±2.0 ml/120 min, p<0.05 between treatments) and a reduction on water intake after AT2 receptors blockade (PD123319:3.5±1.0 vs Control:5.6±1.5 ml/120 min, p<0.05 between treatments). Thus, our results suggest that the AT1 and AT2 receptor in CeA could be part of a integrate circuitry to regulate water and sodium intake caused by extracellular dehydration.